Lippia alba (Mill.) N.E. Britton ex Britton and Wilson, a new addition to the flora of Nepal - Siwakoti, Mohan (Journal of Natural History Museum, 2008)
Lippia alba (Mill.) N.E. Britton ex Britton and Wilson belongs to family Verbenaceae, collected from Rupandehi district of Nepal. It is reported as a new addition to the Flora of Nepal. J. Nat. Hist. Mus. Vol.22, 2005 p.157-158